Analysis of photoinduced electron transfer in flavodoxin - Kiattisak Lugsanangarm (2018)
Flavodoxin (FD) from Desulfovibrio vulgaris, strain Miyazaki F., is a small flavoprotein that is considered to function in the transport of electrons between proteins. The observed fluorescence dynamics of FD revealed two lifetime components, a major (0.92) component at 0.158 ps and a minor (0.08) one at longer than 500 ps. Photoinduced electron transfer (ET) from Trp59 and/or Tyr97 to the excited isoalloxazine (Iso*) in FD were analyzed with atomic coordinates determined by molecula r dynamic simulations (MD), the Kakitani and Mataga ET theory and the observed fluorescence dynamics with and without the minor longer decay component. The observed fluorescence decay with its long tail was not satisfactorily reproduced by the present method. We interpreted the longer lifetime component to be free flavin mononucleotide (FMN) liberated from the protein. The ET rate was faster from Trp59 to Iso* than that from Tyr97 to Iso*, despite the fact that the donor-acceptor distance was shorter in Tyr97-Iso* (mean 0.54 nm) than in Trp59-Iso* (mean 0.64 nm), as elucidated by means of electrostatic (ES) energy. Interactions in the Trp59-Iso*-Tyr97 system were quantum chemically studied using the conformations extracted from 46 MD snapshots at 40 ps time intervals with a PM6 semi-empirical molecular orbital (MO) method of the conformations. Dipole moments of the systems were mostly much greater than that of Iso* alone, and its directions were from Iso* to Trp59. MO analyses revealed that charge transfer takes place mostly from Trp59 to Iso*, which is in accordance with the ET analysis. Correlations between interaction energies and charge density were also examined. Absolute value of the energy increased with amount of the charge transferred. © 2010 Elsevier B.V. All right reserved.